HUBUNGAN TINGKAT EMPATI TERHADAP PERILAKU BULLYING PADA REMAJA MADRASAH TSANAWIYAH - Azizah, Nur; Purwoko, Budi; Christiana, Elisabeth; Setiawati, Denok (Jurnal Penelitian Bimbingan dan Konseling, 2025)
Education in schools plays an important role in improving the quality of human life, but issues such as bullying arise due to a lack of empathy. This study aims to determine the relationship between empathy levels and bullying behavior in middle schools using descriptive quantitative method and Likert scale. Data analysis was conducted using Spearman Rank Correlation. The research results show that empathy influences bullying behavior, with p-value of 0.000 < 0.05 and r-value of -0.464, indicating that higher levels of student empathy correspond to lower occurrences of bullying among students.